1998
DOI: 10.1037/0096-1523.24.3.884
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of intra- and interpersonal interlimb coordination: Coordination breakdowns and coupling strength.

Abstract: Intra-and interpersonal inter]imb coordination of pendulums swung from the wrist was investigated. For both kinds of coordination, the steady state and breakdown of bimanual rhythmic coordination as indexed by the time series of the relative phase angle it were studied under the manipulation of coordination mode, frequency of oscillation, and the difference in the eigenfrequencies (preferred tempos) of the individual oscillating limbs. The properties observed for both intra-and interpersonal coordination were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
163
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 181 publications
(192 citation statements)
references
References 34 publications
(112 reference statements)
25
163
2
1
Order By: Relevance
“…Non-zero mean values of K averaged over all trials indicate emerging interaction between the partners which leads to the observed patterns of synchronization. The regression model employed by Schmidt et al [1998] to measure coupling strength and the extended Kuramoto model proposed in this paper are locally identical, hence the resulting coupling from both task paradigms can be related to each other. The overall mean 3 of 2 |K| (0.52 rad · s −1 ) in Table 1 is about one third of the mean value (1.70 rad · s −1 ) reported by Schmidt et al [1998] for the local model coupling strength of (intentional) interpersonal coordination.…”
Section: Interpretation Of the Modeling Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Non-zero mean values of K averaged over all trials indicate emerging interaction between the partners which leads to the observed patterns of synchronization. The regression model employed by Schmidt et al [1998] to measure coupling strength and the extended Kuramoto model proposed in this paper are locally identical, hence the resulting coupling from both task paradigms can be related to each other. The overall mean 3 of 2 |K| (0.52 rad · s −1 ) in Table 1 is about one third of the mean value (1.70 rad · s −1 ) reported by Schmidt et al [1998] for the local model coupling strength of (intentional) interpersonal coordination.…”
Section: Interpretation Of the Modeling Resultsmentioning
confidence: 99%
“…The regression model employed by Schmidt et al [1998] to measure coupling strength and the extended Kuramoto model proposed in this paper are locally identical, hence the resulting coupling from both task paradigms can be related to each other. The overall mean 3 of 2 |K| (0.52 rad · s −1 ) in Table 1 is about one third of the mean value (1.70 rad · s −1 ) reported by Schmidt et al [1998] for the local model coupling strength of (intentional) interpersonal coordination. Since in their experiments, the participants were instructed to swing pendulums either in in-phase or anti-phase relation, a coupling stronger than in our setting could be expected.…”
Section: Interpretation Of the Modeling Resultsmentioning
confidence: 99%
See 3 more Smart Citations